PENGARUH MODAL, LOKASI DAN JAM KERJA TERHADAP PENDAPATAN PEDAGANG DI PASAR DANGA KABUPATEN NAGEKEO - Tawa, Ines Theresia Bigha; Sayang, Sabulon; Reo, Hermanus (Jurnal Riset Ilmu Akuntansi, 2024)
This study aimed to determine the effect of capital, location, and working hours on the income of Danga market traders, in Nagekeo Regency. The population in this study were all traders in the Danga market, Nagekeo Regency, totalling 1,087 traders. The sample used a purposive sampling method, namely Danga market traders, Nagekeo Regency, with 92 samples. This type of research is quantitative and uses hypothesis testing. This study uses primary data, namely a questionnaire. Data were analyzed using multiple regression analysis which was processed through IMB SPSS Statistics ver 24. The results of this study indicate the value of the t test (1) Capital has a positive and significant effect on the income of traders in the Danga market, Nagekeo Regency. This can be shown by the coefficient value of the capital variable of 0.307 with tcount > ttable (3.500> 1.98729) and a significant level of capital 0.001 <0.05. It means that if the calculated t value is greater than the t table value, then H1 is accepted. (2) Location has a positive and significant effect on the income of traders in the Danga market, Nagekeo Regency. This can be shown by the coefficient value of the location variable of 0.169 with tcount > ttable (2.042>1.98729) and a significant level of location of 0.044 <0.05. It means that if the calculated t value is greater than the t table value, then H2 is accepted. (3) The working hours variable (X3) has no significant effect on the income of traders in the Danga market, Nagekeo Regency. This can be shown by the coefficient value of the working hours variable of 0.133 with tcount < ttable (1.204<1.98729) and a significant level of working hours is 0.232>0.05. It means that if the calculated t value is smaller than the t table value and the significant value is greater than 0.05, then H3 is rejected. Based on the adjusted R2 value of 0.222 or 22.2%, it means that the income variable is influenced by the variable capital, location and working hours of 22.2%. While the remaining 77.8% is influenced by other variables not included in the study.